Exploring Arctic glaciers during the Cold War: continuation of the story - V. N. Mikhalenko (Лëд и снег)
During the cold war, a secret Camp Century military base was created inside the ice sheet in the north-west of Greenland. At this station, the first deep ice core was recovered. It was a beginning of a new era in paleoclimatology – a continuous record of climatic changes over the past 100 thousand years was obtained. At the end of 2018, sediments from the bottom of the Camp Century ice core were discovered at the Niels Bohr Institute in Copenhagen. Their analysis showed that the age of the glacial stratum in this part of Greenland is about 400 thousand years. The history of the Camp Century establishment and glacier ice-core drilling is shown.